Danshen injection ameliorates unilateral ureteral obstruction-induced renal fibrosis by inhibiting ferroptosis via activating SIRT1/GPX4 pathway - Cao, Yiwen; Zhao, Huan; Lin, Shuyin; Chen, Junqi; Xiong, Jingli; Zeng, Zhijun; Long, Ziyu; Su, Yingru; Zhong, Yingqi; Zhao, Lingru; Zhang, Mingshan; Wu, Junbiao; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe pathogenesis of renal fibrosis is related to blood stasis, and the method of promoting blood circulation and removing blood stasis is often used as the treatment principle. Danshen injection (DSI) is a commonly used drug for promoting blood circulation and removing blood stasis in clinic. However, whether DSI slows the progression of renal fibrosis or the potential mechanism is uncertain.MethodsWe investigated renal fibrosis models using UUO mice and TGF-β stimulation in HK-2 cells.ResultsOur findings revealed that DSI or Fer-1 alleviated kidney injury by ameliorating renal morphology injury and pathological injury in vivo. Besides, DSI or Fer-1 inhibited renal fibrosis in vivo and in TGF-β-induced HK-2 cells. Furthermore, ferroptosis was lessened under DSI or Fer-1 treatment. More importantly, the DSI active ingredients (danshensu, salvianolic acid B, protocatechuic aldehyde, caffeic acid and tanshinone IIA) could bind to SIRT1. The protein levels of SIRT1 and GPX4 were downregulated accompanied by the incremental concentrations of TGF-β or Erastin, which were repaired by DSI or Fer-1 intervention. However, the inhibition of ferroptosis and renal fibrosis owing to DSI were reversed by SIRT1 inhibitor EX527.ConclusionTaken together, our results indicated that DSI could protect against ferroptosis to attenuate renal fibrosis by activating the SIRT1/GPX4 pathway. It is expected to be a potential agent to treat renal fibrosis.